Territorial Development Function for the Successful Assignment of TNI AD Soldiers at the Border (Study on the Border of West Kalimantan and NTT) - Suharnoko Suharnoko; Suprapto Suprapto; Makmur Supriyatno; Hikmat Zakky Almubaroq (CV. Rayyan Dwi Bharata, 2023)
TNI law number 34 of 2004 states that one of the TNI's duties is to carry out border security duties. As an elaboration of Law number 34, the TNI Commander issued a policy regarding the implementation of operations, especially border area security operations through the Commander's Regulation (Perpang) number 12 July 2007. The dynamics in the field show that the number of border security unit personnel is still lacking in the face of the vastness of the territory. what they have to protect. For this reason, it is necessary for them to involve the community in participating in border security efforts. The involvement of border communities is very important in supporting the success of the task. In maintaining good relations between the TNI AD and the people, the territorial function which is the function of the TNI AD is the right means. Soldiers must carry out territorial training (Binter) to achieve the unity of the Indonesian Army and the people in order to create security and order in their assigned area. One of the functions of Binter studied was the implementation of territorial attitudes. Writing refers to territorial research in the Badau area, namely the border of West Kalimantan with Malaysia and Motaain on the border of East Nusa Tenggara and Timor Leste. The conclusion from the analysis of the existing data shows that there is a significant influence on the Binter function in this case the territorial attitude on the success of the task where the implementation of the territorial attitude is the gateway to the success of territorial development activities in the assignment area in the framework of border security.